2020
DOI: 10.1371/journal.pone.0238018
|View full text |Cite
|
Sign up to set email alerts
|

Health services costs for lung cancer care in Australia: Estimates from the 45 and Up Study

Abstract: Background Of all cancer types, healthcare for lung cancer is the third most costly in Australia, but there is little detailed information about these costs. Our aim was to provide detailed populationbased estimates of health system costs for lung cancer care, as a benchmark prior to wider availability of targeted therapies/immunotherapy and to inform cost-effectiveness analyses of lung cancer screening and other interventions in Australia. Methods Health system costs were estimated for incident lung cancers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…However, it is important to put this in the context of the potential cost offsets to be gained from facilitating the prevention of smoking related illness. For example, Golsbury et al estimate the average additional health costs for an Australian diagnosed with lung cancer between 45 and 60 years old is AU$67,689 ( 47 ). In addition, a qualitative study among the participants of the present trial reported that the peer researcher and quitline interventions in the Quitlink study have been highly valued as compassionate approaches that have the potential to assist people on a journey to quitting (McCarter et al, submitted 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to put this in the context of the potential cost offsets to be gained from facilitating the prevention of smoking related illness. For example, Golsbury et al estimate the average additional health costs for an Australian diagnosed with lung cancer between 45 and 60 years old is AU$67,689 ( 47 ). In addition, a qualitative study among the participants of the present trial reported that the peer researcher and quitline interventions in the Quitlink study have been highly valued as compassionate approaches that have the potential to assist people on a journey to quitting (McCarter et al, submitted 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have described incremental costs of lung cancer by comparing to a matched control group. In Australia, the healthcare system includes government-funded universal coverage of many medical costs, however less comprehensive than the Danish, and incremental direct costs have been estimated at AU$51,944, excluding patients with previous cancer in their study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some 8379 lung cancer deaths were recorded in 2020 in Australia, and survival from lung cancer remains poor in both males and females with a 5-year survival rate of 20.2%, 3 and lower in New Zealand at 11%. 2 Lung cancer imposes the greatest cancer disease burden, chiefly through years of life lost 4 and direct management costs 5 and is predicted to increase over time. 6 Encouragingly, lung cancer research has seen major advances across the multidisciplinary spectrum over the past decade.…”
Section: Open Accessmentioning
confidence: 99%
“…Additional challenges to modern lung cancer management include the importance of patient-centred and value-based healthcare, rising hospitalisation, management and treatment costs,4 and an ageing population predicted to continue to increase 5 14 15. The opportunities provided by improved diagnostics and therapeutics are in a phase of rapid evolution and for patients to fully benefit from these advances in research evidence there is need for urgent translation of this evidence to routine clinical practice and to acknowledge population health systems in demanding evidence to confirm and guide this translation box 1.…”
Section: Introductionmentioning
confidence: 99%